(3GdEbJUGO GdESdGej hGdbVGjG GdabgjI GdeYGUQIs - (3CMeO Ydj(B, (3GdSGdhSs ((3GdOhMI(B;(3eDSSI GdQjGf(B:s (3OGQ GdKbGaI(B,s, 1998)
(3GdEbJUGO GdESdGej hOhQ Gdabg aj JCUjdg(B- (3eHGOF GdEbJUGO GdESdGej(B- (3OhQ Gdabg aj NUGFU (B-(3OhQ Gdabg aj GdeHGOF(B- (3OhQ Gdabg aj GdfTGW GdEbJUGOj GdeYGUQ(B- (3Mce hOGFY GdHfhc hTgGOGJ GdESJKeGQ aj Gdabg GdESdGej(B- (3GdHfhc hGdESJKeGQ(B- (3GdQO Ydi GdPjf CHGMh aGFOI GdHfhc(B- (3ef GdbVGjG GdabgjI GdeYGUQI(B- (3aJGhi hbQGQGJ GdeLGeY aj GdbVGjG GdabgjI GdeYGUQI(B- (3GdYbhO GdHOjdI ddbQhV GdQHhjI aj GdJWHjb GdeYGUQ(B.s
Keywords: (3GdEbJUGO GdESdGejs